Linear active disturbance rejection-based load frequency control concerning high penetration of wind energy. (1st May 2015) - Tang, Yanmei; Bai, Yan; Huang, Congzhi; Du, Bin
Highlights: A disturbance rejection solution to the load frequency control issue is proposed. Several power systems with wind energy conversation system have been tested. A tuning algorithm of the controller parameters was proposed. The performance of the proposed approach is better than traditional controllers. Abstract: A new grid load frequency control approach is proposed for the doubly fed induction generator based wind power plants. The load frequency control issue in a power system is undergoing fundamental changes due to the rapidly growing amount of wind energy conversation system, and concentrating on maintaining generation-load balance and disturbance rejection. The prominent feature of the linear active disturbance rejection control approach is that the total disturbance can be estimated and then eliminated in real time. And thus, it is a feasible solution to deal with the load frequency control issue. In this paper, the application of the linear active disturbance rejection control approach in the load frequency control issue for a complex power system with wind energy conversation system based on doubly fed induction generator is investigated. The load frequency control issue is formulated as a decentralized multi-objective optimization control problem, the solution to which is solved by the hybrid particle swarm optimization technique. To show the effectiveness of the proposed control scheme, the robust performance testing based on Monte-Carlo approach is carried out. The performance superiority of the system with the proposed linear active disturbance rejection control approach over that with the traditional proportional integral and fuzzy-proportional integral-based controllers is validated by the simulation results.